2012
DOI: 10.4236/anp.2012.13007
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Modified Liposomes for Amyotropic Lateral Sclerosis Therapy: Efficacy in SOD1 Mouse Model

Abstract: Activation of microglia is a histological feature observed in neurodegenerative diseases like ALS. The oral administration of minocycline has been demonstrated to have minimal neuroprotection ability in the animal models and is also associated with inadvertent toxicity due to non-specific oral absorption of the drug. Nonetheless, the drug itself shows promise in a number of disease models suggesting it could be effective if delivered optimally. Thus, we utilized LPS modified liposomes to target TLR4 receptor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Wiley et al designed lipopolysaccharide (LPS)‐modified liposomes targeting TLR4 receptor on the microglia in SOD‐1 mutant mice and loaded them with minocycline demonstrating preferential targeting of microglia cells and a delay in disease progression . Interestingly, the administration of Cu, Zn SOD liposomes favored the delivery of the antioxidant enzyme to the brain, enhancing its protective activity in ischemia/reperfusion injury …”
Section: Nanovectors For Antioxidant Targeting and Deliverymentioning
confidence: 99%
“…Wiley et al designed lipopolysaccharide (LPS)‐modified liposomes targeting TLR4 receptor on the microglia in SOD‐1 mutant mice and loaded them with minocycline demonstrating preferential targeting of microglia cells and a delay in disease progression . Interestingly, the administration of Cu, Zn SOD liposomes favored the delivery of the antioxidant enzyme to the brain, enhancing its protective activity in ischemia/reperfusion injury …”
Section: Nanovectors For Antioxidant Targeting and Deliverymentioning
confidence: 99%
“…For microglial specificity, nanoparticles can leverage receptor-targeting ligands and the inherent phagocytic properties of microglia, while maintaining biocompatibility ( 140 ). An early study of microglial targeting used liposomal nanoparticles modified with the TLR4 ligand lipopolysaccharide (LPS), which significantly increased uptake of the encapsulated drug compared to non-targeted liposomes ( 141 ). In a later study, ceria-zirconia nanoparticles decorated with CD11b antibody showed preferential uptake by microglia compared to other cell types in the brain and higher internalization compared to nanoparticles conjugated to an isotype-matched control antibody ( 142 ).…”
Section: The Prospect Of Nanoparticle Systems For Modulating Immune Cell Polarizationmentioning
confidence: 99%
“…In addition to the use of liposomes as PS carriers, this preparation can be used to deliver a variety of agents including LPS [ 299 ], minocycline [ 299 ], antiinflammatory drugs [ 290 , 300 - 303 ], RGD [ 301 ], enzymes [ 304 - 306 ], fluorescent dyes [ 290 , 291 ], hormones [ 307 , 308 ], antivirals [ 309 ], protease inhibitors [ 310 ], ion-channel modulators [ 311 ], antibiotics [ 312 , 313 ], antioxidants [ 293 , 306 , 314 ], plasmids [ 315 ], signaling-pathway modulators [ 296 ] and toxic compounds [ 292 , 295 , 296 ]. Just to give an example of their use, liposomes containing superoxide dismutase can be incorporated into microglia, which increases their reductive power and favors retinal activity [ 306 ].…”
Section: Liposomes and Alternative Cargo Carriersmentioning
confidence: 99%